Exploring infant gut–derived probiotics through 16S rRNA identification and in vitro functional characterization - Ishita Modasiya; Ritesh Nasit; Harsh Purohit; Apurba Kumar Sarkar; Vijay Kumar (PLoS ONE, 2026)
The infant gut microbiota significantly influences health outcomes, impacting digestion, immunity, and metabolic processes. Identifying beneficial microbes from this source offers promising avenues for novel probiotic development. This study aimed to identify and characterize potential probiotic bacterial isolates from infant fecal samples using 16S rRNA–based identification and in vitro experimental evaluations. A total of 47 isolates were initially screened. Two promising candidates, Lb. paracasei IF5YR and Ent. faecium IF5RW2, were selected and evaluated for gastrointestinal resilience (acid and bile tolerance), functional properties (autoaggregation, cell surface hydrophobicity, bile salt hydrolase activity, antioxidant activity via FRAP, ABTS, and DPPH assays), and safety (antibiotic susceptibility). Their genetic affiliations were confirmed using 16S rRNA sequencing, followed by bioinformatics and phylogenetic analyses. Both Lb. paracasei IF5YR and Ent. faecium IF5RW2 demonstrated strong acid (pH 1.5) and bile (2%) tolerance, high autoaggregation (>70%), and notable cell surface hydrophobicity (>90% for xylene). Comparative analysis of antibiotic susceptibility confirmed their safety. Phylogenetic analysis based on 16S rRNA sequencing supported the taxonomic affiliation of the isolates. Functionally, both strains exhibited bile salt hydrolase activity and strong antioxidant potential, with FRAP values exceeding 75%. These findings suggest Lb. paracasei IF5YR and Ent. faecium IF5RW2 may be considered potential candidates for probiotic applications related to gut health and oxidative stress modulation. They hold potential for development as novel functional food ingredients or health-promoting supplements, although in vivo or clinical studies are needed to confirm any therapeutic effects.